El significado histórico de los Monumentos de la avenida Atahualpa, Riobamba 2016 - Tenemaza Mishque, Sofía Alexandra (2017)
The identity requires tangible presences of those who forged the past, their historical facts and their protagonists are the link between generations and artístíc expressions as sculptures represent the ways to express that identity. In this sense, this research analyzes the historical signifícance of the busts of Atahualpa Avenue in the city of Riobamba, which represent the Shyri Puruhá dynasty and which have a historical and identity vaíue for the citizens population. Based on four objectives: To know the critería of people linked to the historical process and identity of Riobambeños, To understand the meanings of these monuments, through knowing the actions that men and women made in the past, and to establish the conception of population on these facts. As methodological process was established in which, the interviews were carried out with familiar people;with the subject and surveys of citizens who gave the opinion on the matter. Establishing the busts of Atahualpa Avenue are the result of the need to maintain an identity, and although, the history that precedes them to discussed, they represent elements of cultural valué for riobambeños and for Ecuador, however it is relevance it's conservation that has been neglected, it is recommending that the necessary actions could be carried out to maintain them as part of our identity and also to strengthen citizens valúes, However, from these forms of historical cultural expression could be permanent.